2017
DOI: 10.1108/ara-12-2016-0144
|View full text |Cite
|
Sign up to set email alerts
|

Chinese vs US investors’ reactions to accounting narratives: an experiment

Abstract: Purpose The purpose of this paper is to investigate whether investor reactions to accounting narratives are uniform across cultures or if there are predictable systematic culture-based differences, particularly for investors from interdependent cultures, such as in Asia. Design/methodology/approach This research paper builds on the experiment conducted in Riley et al. (2014) by collecting data from investors from interdependent cultures and comparing their investment judgments to the “baseline” judgments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The takeaway for managers seems to be that if they have positive news to convey, they should write with more verbs; however, if they have negative news to convey, they are wise to do so using more nouns/adjectives, as investors will be less likely to punish the firm for this news. However, in an extension to Riley et al (), Yen, Riley, and Liao () found the results only hold for investors from Western cultures, such as the United States. Investors from Eastern cultures, such as China, have a preference for and familiarity with concrete language, based on the prevalence of its use in these cultures.…”
Section: Abstract Versus Concrete Languagementioning
confidence: 87%
“…The takeaway for managers seems to be that if they have positive news to convey, they should write with more verbs; however, if they have negative news to convey, they are wise to do so using more nouns/adjectives, as investors will be less likely to punish the firm for this news. However, in an extension to Riley et al (), Yen, Riley, and Liao () found the results only hold for investors from Western cultures, such as the United States. Investors from Eastern cultures, such as China, have a preference for and familiarity with concrete language, based on the prevalence of its use in these cultures.…”
Section: Abstract Versus Concrete Languagementioning
confidence: 87%
“…Martinov and Mladenovic (2013) test incorporation of ethical framework in ethical education for first-year accounting students. Finally, Tsunogaya, et al (2016) and Yen, et al (2017) examine how environment such as colleague and culture affect our decision making process.…”
Section: Situation/environmentmentioning
confidence: 99%